Awareness and perception of physicians about forgery and counterfeiting in the medical field in Egypt - Ahmed Salah Elsayed; Marwa Ali Mwaheb; Asmaa Yonis Elsary; Khaled El Rashed; Amal R. Saleh (Scientific Reports)
Abstract Medical records may act as one of the legal pieces of evidence in the court. A complete and correct medical record contains a chronological health history of the patient, and it is one of the keys to resolving cases of alleged malpractice. The aim is to emphasize the importance of strict rules and training to ensure medical documents are handled properly and the prevalence of signature forgery in medical reports. This cross-sectional descriptive study was conducted with a sample of 300 randomly selected physicians from hospitals in Fayoum, Egypt, between 2024 and 2025. According to the opinions of 133 physicians (44.3%), forgery and counterfeiting are relatively common in the medical sector; 81 physicians (27%) believed it is common, and 9 physicians (3%) considered it very common, especially in medical reports. 186 (75.6%) were forged medical reports. 185 (61.7%) blamed it on inadequate supervision, while 162 (54%) said it was done to get money. This is followed by 160 doctors (53.3%) who cite respect for the senior and following his instructions if asked to signature in place. Importantly, the overwhelming support for enhanced oversight and education indicates a collective recognition of the necessity for systemic changes to combat forgery in the medical field.